Measurements of water-mass properties with a glider in the South-western Adriatic Sea. (12th February 2016) - Mauri, E.; Gerin, R.; Poulain, P.-M.
ABSTRACT: A glider was operated between 15 and 22 May 2013 off the Puglia coast in the southwestern Adriatic Sea in order to describe the spatial structure of the water-mass properties related to mesoscale eddies generated by the Western Adriatic Current and investigate the presence of deep water formed in the Northern Adriatic Sea. Temperature, salinity, chlorophyll concentration (CHL), dissolved oxygen and backscattering were measured between the surface and depths as large as 900 m. The glider in situ measurements revealed enhanced mesoscale variability at scales of days and 5–10 km. In particular, on 19 May 2013, a water mass with a density similar to the deepest waters in the Northern Adriatic was sampled at a depth of 200 m.